The base-promoted synthesis of multisubstituted benzo[b][1, 4]oxazepines. Issue 16 (18th January 2016) - Shen, Jinhai; Xue, Lulu; Lin, Xing; Cheng, Guolin; Cui, Xiuling
Abstract : A variety of substituted benzo[ b ][1, 4]oxazepines have been prepared via base-promoted intramolecular O -arylation from N -(2-haloaryl)enaminones under metal-free conditions. Abstract : A novel protocol to synthesize multisubstituted benzo[ b ][1, 4]oxazepines from N -(2-haloaryl)enaminones has been developed. In this procedure, only 2 equiv. of Cs2 CO3 was required. A variety of polysubstituted benzo[ b ][1, 4]oxazepine derivatives were provided in up to 95% yield for 27 examples.